2018
DOI: 10.3390/fractalfract2020016
|View full text |Cite
|
Sign up to set email alerts
|

The Craft of Fractional Modeling in Science and Engineering 2017

Abstract: Fractional calculus has performed an important role in the fields of mathematics, physics, electronics, mechanics, and engineering in recent years. The modeling methods involving fractional operators have been continuously generalized and enhanced, especially during the last few decades. Many operations in physics and engineering can be defined accurately by using systems of differential equations containing different types of fractional derivatives.This book is a result of the contributions of scientists invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…where R(α i ) is a normalization constant. This choice corresponds to the Caputo-Fabrizio [59][60][61]. A remarkable feature of this exponential kernel is its connection with resetting processes [61].…”
Section: Generalized Comb-models With Fractional Operatorsmentioning
confidence: 99%
“…where R(α i ) is a normalization constant. This choice corresponds to the Caputo-Fabrizio [59][60][61]. A remarkable feature of this exponential kernel is its connection with resetting processes [61].…”
Section: Generalized Comb-models With Fractional Operatorsmentioning
confidence: 99%
“…In this paper we have considered only fractional differential equations of Riemann-Liouville type. But many real-world processes can be better modelled using other definitions of fractional calculus: for example, the Caputo definition ( 7) is better suited to many initial value problems, and newer definitions such as Caputo-Fabrizio and Atangana-Baleanu have been used to model various types of nonlocal dynamics [6,7,18]. Solving fractional PDEs in these alternative fractional models could be an important result, and it may be possible to do so using the unified transform method.…”
Section: Potential Extensionsmentioning
confidence: 99%
“…In the last few decades, continuous generalization and enhancement of fractional operators have been noticed due to their hereditary properties and material memory effects. Recently, it has been demonstrated that the fractional calculus 33 has an involvement in the modeling of differential equations (DE’s) of non-integer order. Studies reveal that these fractional differential equations can describe more accurately the dynamics of many systems.…”
Section: Introductionmentioning
confidence: 99%